A bi-planar coil system for nulling background magnetic fields in scalp mounted magnetoencephalography - Holmes, Niall; Leggett, James; Boto, Elena; Roberts, Gillian; Hill, Ryan M.; Tierney, Tim M.; Shah, Vishal; Barnes, Gareth R.; Brookes, Matthew J.; Bowtell, Richard (Elsevier, 2018)
Small, commercially-available Optically Pumped Magnetometers (OPMs) can be used to construct a wearable Magnetoencephalography (MEG) system that allows large head movements to be made during recording. The small dynamic range of these sensors however means that movement in the residual static magnetic field found inside typical Magnetically Shielded Rooms (MSR) can saturate the sensor outputs, rendering the data unusable. This problem can be ameliorated by using a set of electromagnetic coils to attenuate the spatially-varying remnant field. Here, an array of bi-planar coils, which produce an open and accessible scanning environment, were designed and constructed. The coils were designed using a harmonic minimisation method previously used for gradient coil design in Magnetic Resonance Imaging (MRI). Six coils were constructed to null